Origins of classical architecture temples, orders and gifts to the gods in ancient Greece - Wilson Jones, Mark 1956- (Yale University Press, 2014)
Purpose and setting of the Greek temple -- Formative developments -- Questions of construction and the Doric genus -- Questions of influence and the Aeolic capital -- Questions of appearance and the Ionic genus -- Questions of meaning and the Corinthian capital -- Gifts to the gods -- Triglyphs and tripods -- Crucible -- Questions answered and unanswered